The impact of movement-based games on the development of physical qualities in 5–6-year-old children in Vietnam: A case study at 19/5 kindergarten, Thai Nguyen city - Quynh, Dao Thi Hoa; Cuong, Do Ngoc (International Journal of Innovative Research and Scientific Studies, 2025)
Movement-based games (MBGs) are considered an effective means of physical education, especially in developing physical fitness among preschool children. The purpose of this study is to evaluate their effectiveness in enhancing the physical qualities of children aged 5–6 years. A total of 60 healthy children aged 5–6 were randomly selected and divided into two groups: an experimental group (EG) with 30 children, who participated in movement-based games designed by the research team, and a control group (CG) with 30 children, who followed the school’s standard physical activity program. This study employed six criteria to assess the development of physical fitness qualities in 5–6-year-old children, including: 18-meter sprint; dominant-hand distance throw; standing long jump; ball bouncing and catching; one-leg balance; and a 75-second endurance run. The results after 12 weeks of applying MBGs show that the experimental group achieved higher growth rates across all six physical fitness tests compared to the control group. Among these, the throwing and catching ball test showed the highest improvement at 35.17%, while the standing long jump recorded the lowest increase at 8.66%. Although the control group also exhibited some changes in physical qualities between the pre-test and post-test, these differences were not statistically significant (p > 0.05). These results demonstrate that the use of movement-based games (MBGs) is more effective in improving children’s physical fitness than the current educational program. We recommend actively integrating MBGs into the teaching process to enhance the quality of physical education in preschools.